Адміністративно-правові основи застосування захисних заходів у зовнішній торгівлі - Панфілова, Ольга Євгенівна; Панфилова, Ольга Евгеньевна; Panfilova, Olga E. (My University, 2013)
Дисертація на здобуття наукового ступеня кандидата юридичних наук за спеціальністю 12.00.07 - адміністративне право і процес; фінансове право; інформаційне право. - Національний університет «Одеська юридична академія», Одеса, 2013. На основі аналізу національного, міжнародного та зарубіжного законодавства здійснено аналіз правової природи застосування захисних заходів у зовнішній торгівлі, надано загальну оцінку доцільності їх застосування, визначено їх місце у митному регулюванні та виявлено особливості, властиві спеціальним митам. Встановлено коло міжнародних і національних правових актів, які формують законодавчу базу регулювання захисних заходів. Проаналізовано структуру інституціонального механізму застосування спеціальних заходів на національному та міжнародному рівнях. Визначено основні принципи та стадії спеціального розслідування та з'ясовано особливості справляння спеціальних мит під час процедур митного оформлення та митного контролю.

Диссертация на соискание научной степени кандидата юридических наук по специальности 12.00.07 - административное право и процесс, финансовое право, информационное право. - Национальный университет «Одесская юридическая академия», Одесса, 2013. В исследовании на основе анализа национального, международного и зарубежного законодательства осуществлен комплексный анализ правовой природы применения защитных мер во внешней торговле, дана общая оценка целесообразности их применения, определено их место в таможенном регулировании и выявлены особенности, присущие специальным мерам. Установлен круг международных и национальных правовых актов, которые формируют законодательную базу регулирования защитных мер. Проанализирована структура институционального механизма применения специальных мер на национальном и международном уровне. Определены основные принципы и стадии специального расследования, выяснены особенности применения специальных пошлин во время процедур таможенного оформления и таможенного контроля.

Thesis for Candidate of Law's degree on specialization 12.00.07. — Administrative Law and Process; Financial Law; Informational Law. - National University "Odessa Law Academy", Odessa, 2013. The present research, based on comprehensive analysis of the customs legislation of Ukraine and the leading countries of the world, national and international law enforcement activities, scientific papers and publications in the field of customs law, provides the complex analysis for the of legal nature of safeguard measures in international trade, defined the place in the customs regulation. The structure of the institutional mechanism for application of safeguards at the national and international level was analyzed. The research also clarified particular collection of safeguard measures during the procedures of customs control. One of the goals of the work is a detailed study of the safeguard measures in a historical context. The basic stages of the protective measures in foreign trade as the instalment of customs regulations and the characteristics of their regulative effect on foreign relations are shown in the work. The author analyzes the main legal acts, contracts, and various stages of reform legislation and rounds of GATT negotiations, which have influenced the formation of safeguard measures. Also this study holds the link and explores the historical impact of each of these components on the current state of the protective measures. In this work the structure of a special investigation, consisting of a sequence of obligatory and optional steps are described. The peculiarities of the legal nature of protective measures are shown on the one hand as the exception to the international legal obligations of the foreign trade regime, on the other as exception to the general rules on tariff and non-tariff regulation. The basic characteristics of protective measures are determined as: temporality, non- discrimination, proportion al ity. The specific of application of safeguard measures of customs policies is studied in accordance with international principles of foreign trade. Basically, author considers the narrow sense of the importance for the principle of "proportionality" by examining its contents as a general principle of law, international law and WTO law. Also the work defines the principles of special investigation, which revealed its peculiarities and specificity as a particular type of administrative procedure: rule of law, taking into account national interests, formality, openness, transparency and international cooperation. The work analyzes the legal basis of the customs control and clearance of the goods, which are the subject of safeguard measures; problems of specific customs procedures and solutions to improve national legislation in this field. Particular attention is paid to the decision of the Interdepartmental Commission on International Trade in collecting special duties, and the correct classification of the product and determining the country of origin for customs control. In the course of the study particular attention is paid to investigation of the use of special procedures in the United States and Canada. Based on comparative analysis of systems and the application of protective measures U.S., Canada and Ukraine, the author revealed specificity of common international standards: quasi-judicial nature of the body that conducts the investigation, extensive interaction authorities. During the study of foreign experience the author carried out a detailed analysis of both the overall institution mechanism for the implementation of measures and the role of each organ in system. Particular attention is given to the functions of the President and his influence on the outcome of the investigation. The study addresses the issue of the rare use of safeguards and, as the cause of the phenomenon, the problem of putting into practice the provisions of the law on the use of compensation. The improving of views on the structure of institutional mechanism to use a special duty in Ukraine, functions and powers of the relevant authorities helped formulate proposals for its improvement; approaches to the role of special duties in determining the structure of imports, its strengths and weaknesses in relation to other means of protecting the domestic market; position of the necessity of applying the general principles of administrative law during special investigations and appropriate provisions in the legislation. The paper has expanded the range of terms associated with the use of safeguard measures in foreign trade, the definition of safeguard measures based on international standards; approaches to determining the reasons and ways of practical implementation of protective equipment in foreign trade and taking into account the principle of national interests in decision-making process.
Панфілова О. Є. Адміністративно-правові основи застосування захисних заходів у зовнішній торгівлі : автореф. дис. ... канд. юрид. наук : 12.00.07 / О. Є. Панфілова; кер. роботи Б. А. Кормич; Нац. ун.-т "Одеська юридична академія". – Одеса, 2013. – 21 с.
Keywords: захисні заходи; спеціальні мита; особливі мита; спеціальне розслідування; зовнішня торгівля; інституціональний механізм; митний контроль; митне оформлення; міжнародно-правові стандарти; защитные меры; специальные пошлины; особенные пошлины; специальное расследование; внешняя торговля; институциональный механизм; таможенный контроль; таможенное оформление; международно-правовые стандарты; safeguard measures; safeguard duties; special investigations; foreign trade; institutional mechanism; customs control; customs clearance; international legal standards